Juridical Analysis Of Suspect Determination Procedures Police Investigators Against Criminal Offenders (Research Study In Barelang Police) - Oyong Wahyudi; Fadlan Fadlan; Dahlan Dahlan; Erniyanti Erniyanti; Soeryo Respatino (International Journal of Education, Language, Literature, Arts, Culture, and Social Humanities, 2023)
The determination of a suspect must be in accordance with applicable legal provisions based on 2 (two) valid pieces of evidence, namely witness statements obtained by the investigator, expert statements obtained by the investigator, letters, and instructions for each piece of evidence obtained by the investigator through an in-depth examination. The investigator's coercive actions must be carried out responsibly according to the law and legal provisions so that arbitrary actions do not occur against the suspect's freedom, independence, and human rights. The problem in this research is the law, implementation, and what factors become obstacles and obstacles in the process of determining suspects for perpetrators of criminal acts. This research uses a descriptive analysis method using a normative approach (legal research) and is supported by empirical research. This was carried out to obtain primary data obtained through interviews through field research. The results of this study explain that the Criminal Procedure Code (KUHAP) has clearly and firmly regulated matters relating to the rights of suspects. The rights of suspects regulated in the Criminal Procedure Code are Priority Rights for Case Settlement, this has been emphasized in Article 50 of the Criminal Procedure Code (KUHAP) which reads: a) A suspect has the right to immediately be examined by investigators, then can be submitted to the Public Prosecutor. b) The suspect has the right to immediately bring his case to court by the public prosecutor. c) The accused has the right to be tried immediately by the Court., The right to prepare a defense, the right to get an interpreter, and the right to choose their own legal adviser The purpose of this right is to get legal counsel in accordance with the provisions of Article 54 of the Criminal Procedure Code for suspects. For this reason, it is expected that in determining the suspect to have qualified investigators they pay attention to the following matters: Have general knowledge, Knowledge is quite broad, where Investigating Officers are required to have knowledge that is quite extensive, Confident in themselves. Investigating Officers must have high self-confidence, have character, be professional, understand psychology practically, be brave, honest, talented actor, wise, alert, and experienced. Courage, honesty, wisdom, and vigilance are needed in the examination process by an investigating officer. Experience Investigating officers must be experienced in order to master psychology/psychology and be able to act in acting is also very important to have.